Предмет: Математика, автор: xomka12332

Упростите выражение
(4b/(4-b)+16/(16-b^2))(4+b)/4-4/(4-b)

Ответы

Автор ответа: MizoriesKun
1

Смотри........................

Приложения:
Автор ответа: IrkaShevko
1

Ответ:

Пошаговое объяснение:

(\dfrac{4b}{4-b}+\dfrac{16}{(4-b)(4+b)})*\dfrac{4+b}{4} -\dfrac{4}{4-b} =\\\\=(\dfrac{16b+4b^2+16}{(4-b)(4+b)})*\dfrac{4+b}{4} -\dfrac{4}{4-b} =\\\\=\dfrac{(b+2)^2}{4-b} -\dfrac{4}{4-b} =\\\\=\dfrac{4b+b^2+4-4}{4-b}=\\\\=\dfrac{b(4+b)}{4-b}

Похожие вопросы
Предмет: Математика, автор: pozdnakovtema49
Предмет: Физика, автор: 123105949
Предмет: Математика, автор: ЮРАС0000000001